2015
DOI: 10.1111/and.12405
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of phosphodiesterase type 5 (PDE5) inhibitors in treating erectile dysfunction after bilateral nerve-sparing radical prostatectomy

Abstract: We carried out a systematic review and meta-analysis to assess the efficacy and safety of phosphodiesterase type 5 (PDE5) inhibitors for treating erectile dysfunction (ED) after bilateral nerve-sparing radical prostatectomy (BNSRP). A literature review was performed to identify all published randomised double-blind, placebo-controlled trials of PDE5 inhibitors for the treatment of ED after BNSRP. The search included the following databases: MEDLINE, EMBASE and the Cochrane Controlled Trials Register. The refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…Both the previous meta-analysis 29 30 31 and ours revealed that a larger portion of ED patients considerably benefited from PDE5-Is intervention when compared with placebo. After stratified by various drugs, we found that all four drug regimen ameliorated IIEF score compared with placebo both in the network and pairwise meta-analysis.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Both the previous meta-analysis 29 30 31 and ours revealed that a larger portion of ED patients considerably benefited from PDE5-Is intervention when compared with placebo. After stratified by various drugs, we found that all four drug regimen ameliorated IIEF score compared with placebo both in the network and pairwise meta-analysis.…”
Section: Discussionsupporting
confidence: 48%
“…Inextricably associating the medication with a man’s sexual performance, PDE5-Is for ED have empirically been used just before a sexual encounter 32 . Pharmacokinetic studies of tadalafil confirmed that the steady state is reached after five day of daily use 30 32 . A total tadalafil plasma concentration of 55 ng/ml constituted a reasonable pharmacodynamic target, suggesting the maintenance of these concentrations throughout the dosing interval of 24 h 33 .…”
Section: Discussionmentioning
confidence: 84%
“…Both the previous meta-analysis [29][30][31] and ours revealed that a larger portion of ED patients considerably benefited from PDE5-Is intervention when compared with placebo. After stratified by various drugs, we found that all four drug regimen ameliorated IIEF score compared with placebo both in the network and pairwise meta-analysis.…”
Section: Discussionmentioning
confidence: 48%
“…Pharmacokinetic studies of tadalafil confirmed that the steady state is reached after five day of daily use 30,32 . A total tadalafil plasma concentration of 55 ng/ml constituted a reasonable pharmacodynamic target, suggesting the maintenance of these concentrations throughout the dosing interval of 24 h 33 .…”
Section: Discussionmentioning
confidence: 83%
“…Erectile function is an important issue for both men who have undergone RP (Chartier‐Kastler et al ., ) and the general population (Jannini, ; Jannini et al ., ; Lombardi et al ., ), and clinicians tend to underestimate patients’ distress and desire for early treatment (Jannini et al ., , ). Although a number of recent systematic reviews have addressed the role of PDE5Is in the post‐surgery setting (Miles et al ., ; Li et al ., ; Wang et al ., ; Cui et al ., ), none has comprehensively and systematically investigated if (i) PDE5Is aid drug‐assisted and unassisted EF recovery, (ii) PDE5I half‐life and (iii) different PDE5I active ingredients affects clinical efficacy in relation to treatment modality, or (iv) the time from surgery to inhibitor administration has a clinical impact on post‐surgery EF recovery. When oral PDE5Is were used to manage post‐BNSRP ED, their efficacy in recovering drug‐assisted EF was demonstrated with respect to placebo.…”
Section: Discussionmentioning
confidence: 99%